Deciphering how LIP2 and POX2 promoters can optimally regulate recombinant protein production in the yeast Yarrowia lipolytica. Issue 1 (December 2016) - Sassi, Hosni; Delvigne, Frank; Kar, Tambi; Nicaud, Jean-Marc; Coq, Anne-Marie; Steels, Sebastien; Fickers, Patrick
Abstract Background In recent years, the non-conventional model yeast speciesYarrowia lipolytica has received much attention because it is a useful cell factory for producing recombinant proteins. In this species, expression vectors involvingLIP2 andPOX2 promoters have been developed and used successfully for protein production at yields similar to or even higher than those of other cell factories, such asPichia pastoris . However, production processes involving these promoters can be difficult to manage, especially if carried out at large scales in fed-batch bioreactors, because they require hydrophobic inducers, such as oleic acid or methyl oleate. Thus, the challenge has become to reduce loads of hydrophobic substrates while simultaneously promoting recombinant protein production. One possible solution is to replace a portion of the inducer with a co-substrate that can serve as an alternative energy source. However, implementing such an approach would require detailed knowledge of how carbon sources impact promoter regulation, which is surprisingly still lacking for theLIP2 andPOX2 promoters. This study's aim was thus to better characterize promoter regulation and cell metabolism inY. lipolytica cultures grown in media supplemented with different carbon sources. Results pPOX2 induction could be detected when glucose or glycerol was used as sole carbon source, which meant these carbon source could not prevent promoter induction. In addition, when a mixture of glucose and oleic acid was used in complex medium, pPOX2 induction level was lower that that of pLIP2 . In contrast, pLIP2 induction was absent when glucose was present in the culture medium, which meant that cell growth could occur without any recombinant gene expression. When a 40/60 mixture of glucose and oleic acid (w/w ) was used, a tenfold increase in promoter induction, as compared to when an oleic-acid-only medium was observed. It was also clear that individual cells were adapting metabolically to use both glucose and oleic acid. Indeed, no distinct subpopulations that specialized on glucose versus oleic acid were observed; such an outcome would have led to producer and non-producer phenotypes. In medium containing both glucose and oleic acid, cells tended to directly metabolize oleic acid instead of storing it in lipid bodies. Conclusions This study found that pLIP2 is a promoter of choice as compared to pPOX2 to drive gene expression for recombinant protein production byY. lipolytica used as cell factory.